2009
DOI: 10.1186/1471-2164-10-515
|View full text |Cite
|
Sign up to set email alerts
|

SnoRNAs from the filamentous fungus Neurospora crassa: structural, functional and evolutionary insights

Abstract: BackgroundSnoRNAs represent an excellent model for studying the structural and functional evolution of small non-coding RNAs involved in the post-transcriptional modification machinery for rRNAs and snRNAs in eukaryotic cells. Identification of snoRNAs from Neurospora crassa, an important model organism playing key roles in the development of modern genetics, biochemistry and molecular biology will provide insights into the evolution of snoRNA genes in the fungus kingdom.ResultsFifty five box C/D snoRNAs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 62 publications
(90 reference statements)
0
27
0
Order By: Relevance
“…The genome-wide analysis of chicken snoRNAs provided direct evidence for extensive recombination and separation of guiding function [34]. Similarly, multicellular fungi exhibit a more complex pattern of methylation guided by box C/D snoRNAs than unicellular yeasts [35]. Nevertheless, conserved snoRNA targets typically have conserved modification sites, although there is some redundancy and an appreciable level of turnover throughout the animal kingdom [32].…”
Section: Introductionmentioning
confidence: 99%
“…The genome-wide analysis of chicken snoRNAs provided direct evidence for extensive recombination and separation of guiding function [34]. Similarly, multicellular fungi exhibit a more complex pattern of methylation guided by box C/D snoRNAs than unicellular yeasts [35]. Nevertheless, conserved snoRNA targets typically have conserved modification sites, although there is some redundancy and an appreciable level of turnover throughout the animal kingdom [32].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 11 of these spliced, noncoding RNAs revealed that their exons have no apparent function, but that their introns contain C/D box snoRNAs—noncoding RNAs that target modifications to ribosomal RNA (rRNA) (11). In the nonhemias-comycetous fungus Neurospora crassa , snoRNAs are also generally processed from the introns of non-protein-coding precursors (12). This is different, however, from the more closely related hemiascomycete S. cerevisiae , where nearly all snoRNAs arise from unspliced primary transcripts and, therefore, require a splicing-independent processing pathway (13).…”
mentioning
confidence: 99%
“…A 1-kb flank sequence upstream of the RP genes were used to search for Homol-D sites. Box C/D snoRNAs in S. cerevisiae, A. fumigatus, N. crassa, C. albicans, D. hansenii, K. lactis, K. waltii, Y. lipolytica, and Z. rouxii were collected from previous studies-S. cerevisiae from SGD (Cherry et al 2012), A. fumigatus from Jöchl et al (2008); N. crassa from Liu et al (2009); and others from Mitrovich et al (2010). A 1-kb flank sequence upstream of the mono-independent transcription snoRNAs, of the first snoRNA member (for snoRNA clusters), or of the host protein-coding genes (for snoRNAs coded in protein-coding gene introns) were chosen for Homol-D box searching.…”
Section: Prediction and Detection Of Methylated Nucleotide Sites In Rrnamentioning
confidence: 99%